Carbon sequestration and trace gas emissions in slash-and-burn and alternative land uses in the humid tropics - Palm, C. A.; Woomer, P. L.; Alegre Horihuela, Julio; Arévalo López, Luis Alberto; Castillo Cobella, Carlos; Cordeiro, D. G.; Hairiah, K.; Kotto Same, J.; Njomgang, R.; Ricse Tembladera, Auberto; Rodrigues, V.; Van Noordwijk, M. (ASB climate change working group, 2019)
39 páginas